If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + 4c = 61x Solving 45 + 4c = 61x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + 4c = -45 + 61x Combine like terms: 45 + -45 = 0 0 + 4c = -45 + 61x 4c = -45 + 61x Divide each side by '4'. c = -11.25 + 15.25x Simplifying c = -11.25 + 15.25x
| Z/16w=40 | | 2x+-5=5x+28 | | 7=7(-9-4) | | 4s+14=6s-6 | | 16m-5(2m-3)=33 | | 1.5(x+5)=-(3x+15) | | 6y-15=19y | | 7=7(2-4) | | c+11=11c-19 | | X(2x+8)=3x-4 | | 69.4/4 | | 4km2/12k | | 41s-6=38s | | 24b-36=6b | | 0=9w^2-30w+25 | | X(2x+8)=(3x-4) | | 3x-8=44-X | | 8y-11=6y+7 | | 4(2k+1)-18=26 | | 24/x=16 | | 15y+12=11y+20 | | 2cos^2x-sinx-1=0 | | 12(v+4)-3v=3(3v+3)-18 | | 0=4u^2-15u-4 | | 16q-10=14q | | 1/2x-2=2x-1/2 | | 15m+8=10m-7 | | 2p-14=p+16 | | c-3=2c-12 | | -8t=4t+5+2t | | 7.8×9/4 | | 18v=14v+16 |